The Influence of Knowledge, Attitudes and Behavior of Cleaning Officers with the Number of Mosquito Larvae in the Water Reservoir Punti Kayu Palembang City - Aldi Alfian; Chairil Anwar; Iche Andriyani Liberty (HM Publisher, 2021)
Background Mosquito was one of the animals that can transmit deadly diseases.Information about water reservoirs as their habitat as well as human knowledge,attitudes and behavior factors are considered important to help eradicate mosquito.This study aims to determine the effect of knowledge, attitudes and behavior ofcleaners on the number of mosquito larvae in water reservoirs in Palembang.Methods This research was mixed method research (quantitative and qualitative) inthe field and laboratory. The research samples were all mosquito larvae andcontainers found. The research respondents were all cleaning services. Data werecollected by interviewing and filling in questionnaires, observing water reservoirsand identifying the types of mosquito larvae in microscope. Results A total of 40containers were found in Punti Kayu Nature Park. There were 8 containers that wereindoors (20%) and 32 containers were outdoors (80%) with 17 containers containedlarvae. Of all the containers that were positive for larvae, 6 were filled with clearwater and 11 were filled with turbid water. The number of larvae found were 358larvae outdoors and 82 larvae indoor with a total of 440 mosquito larvae with thegenus Culex spp. and Aedes albopictus species. The index of mosquito larvae wereobtained FLI (Free Larva index)=66,67%, HI (House Index)=33,33%, CI (ContainerIndex)=16,67%, BI (Breteau Index)=33.33% from the 3 buildings examined. Fromthese results, it was obtained DF (density figure) or density level of 5. There were 40containers that could be habitats for Culex spp. and Aedes albopictus. ConclusionThe knowledge, attitude and behavior of the cleaning services were good. Thenumber of mosquito larvae could be influenced by the frequency of cleaning and thelack of knowledge of the cleaning services.